The microbiological and metabolic traits associated with pT3 colorectal cancer metastasis to lymph nodes - Chen, Lei; Zhang, Yiwen; Wang, Yilin; Cao, Dianbo; Tai, Jiandong; Gao, Kaiyue (Frontiers in Physiology, 2025)
IntroductionGut microbiota and metabolites play a crucial role in the progression of colorectal cancer. Over half of the CRC patients are at pT3 stage, the presence or absence of regional lymph node metastasis in pT3 patients significantly influences both treatment strategies and prognosis. However, the associations between these are not been revealed yet. It is crucial to gain a deeper insight into the mechanisms underlying the differences in gut microbiota and metabolites between pT3 CRCs with and without lymph node metastasis.MethodsWe processed 16S rRNA gene sequencing and ultrahigh-performance liquid chromatography–mass spectrometry in 70 pT3NxM0 CRC patients. In addition, transcriptomic data from TCGA were retrieved to assess RNA expression differences between the two groups for a comprehensive comparison. Finally, correlation analyses of microbiota, metabolome and transcriptomic data were performed to identify meaningful connections and mechanisms underlying lymph node metastasis.ResultsA total of 192 metabolites were different between the patients with and without lymph node metastasis; among these metabolites, 94 upregulated different metabolites were enriched in biological processes of tumor progression. The gut microbiota of lymph node positive CRCs is characterized by increased abundances of cancer progression, such as Proteobacteria. We identified 226 differentially expressed genes from TCGA-CRC cohort, among which the upregulated genes were mainly involved in pathways of cancer progression, proliferation, migration, and invasion, while downregulated genes were significantly enriched in pathways of tyrosine metabolism and immunity. The cross-correlation analysis showed that the altered metabolites and genes were enriched in neuroactive ligand receptor interaction pathway.ConclusionOur study identified key microbiota and metabolites associated with lymph node metastasis in pT3 colorectal cancer, along with potential pathways and interactions implicated in the lymph node metastasis.